Molluscicidal Efficacy of Vitellaria paradoxa (Shea Butter) Leaf extracts on Schistosoma haematobium Snail Host, Bulinus globosus (Sahel Journal of Life Sciences FUDMA, 2025)
Schistosomiasis is considered as one of the most important trematode diseases of man. This research was conducted to determine the phytochemical components and molluscicidal efficacy of methanol and aqueous extracts of Vitellaria paradoxa.  Molluscicidal efficacy of the plant was tested on Bulinus globosus, the Schistosoma haematobium host snail species.  The molluscicidal activity was assessed by determining the efficacy of various graded concentrations (0, 16, 32, 64 and 128mg/L) of the aqueous and methanol extracts. The crude extract collected from the plant was screened for phytochemicals and the result revealed the presence of Alkaloids, Tannins, Saponins, Oxalate, Flavonoid, Steroid, Terpene, Phlobotannin, Cardiac glycoside and Anthraquinone illustrating that there are bioactive components in the plant. The molluscicidal test showed that the mortality was dose â€“ dependent. The highest molluscicidal activities were recorded at 64mg/L at 4hours and 128mg/L at 1hour of exposure to the methanol extract as well as 64mg/L at 24hours and 128mg/L at 12hours of exposure to the aqueous extract. The LC50 and LC90 of the methanol extract at 24hours were 20.74 and 53.92mg/L and at 48hours were 0.00 and 49.65 while the LC50 and LC90 of the aqueous extract at 24hours were 22.22 and 3.11mg/L and at 48hours were 1.81 and 2.95mg/L respectively. The result obtained showed that both extracts had significant (p